Risk Identification for the Construction of Public-Private Partnership (PPP) Housing In Malaysia - Putri Zulaiha, Razi; Noram Irwan, Ramli; Mohamad Idris, Ali (Kaav Publications, 2018)
The construction project is quite complex and involves many stages of the process as well as various parties involved in the realization of a construction project whether from the industry itself or the authorities. This work is a preparatory from the full length studies that aiming in developing a risk management framework for PPP Housing. This study is conducted after seen the necessary of a systematic analysis of risk in construction delay from cradle to grave i.e pre-construction to post-construction stages. Nevertheless, this study aim to develop a clear understanding among construction industry players and professionals in Malaysia. It is therefore important to find the risk factors that led to the delay and multiple parties involved that causing the delay.